IMPLEMENTASI ASESMEN MATEMATIKA BERBASIS PENDEKATAN CULTURALLY RESPONSIVE TEACHING DALAM MENINGKATKAN KETERAMPILAN LITERASI MATEMATIS SISWA SD: - - Rifqi Al Farizza; Kartika Arlianasari Nurrohmah; Kusumawati Shindi Nur Rahmawati; Ade Eka Anggraini; Siti Faizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of mathematics assessment based on the Culturally Responsive Teaching (CRT) approach and to analyze its effect on the mathematical literacy skills of third-grade elementary school students. The study employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest model. The subjects consisted of 28 third-grade students from a elementary school in Malang, selected through purposive sampling. The research instrument was an multiple choice test designed to measure three indicators of mathematical literacy: the ability to identify relevant information, explain problem-solving processes in their own words, and present mathematical ideas in a structured manner. Data were analyzed using the Shapiro-Wilk normality test, t-test, and the non-parametric Wilcoxon Signed-Rank Test with the assistance of SPSS version 29. The results showed that the data were not normally distributed; therefore, the Wilcoxon test was used, yielding a significance value of 0.001 < 0.05, indicating a significant effect of CRT-based assessment on students’ mathematical literacy skills. Improvement was also evident from the increase in the mean score from 46.7 in the pretest to 68.5 in the posttest. The implementation of CRT-based assessment was carried out by integrating local cultural elements, such as the Bapang Mask Dance and temple architecture, into angle measurement materials. This approach proved effective in enhancing conceptual understanding, student engagement, and the ability to communicate mathematical ideas contextually. Thus, CRT-based mathematics assessment is effective in improving elementary students’ mathematical literacy skills.